Radioactivity measurements in epiphytic lichens of Uludağ Mountain in Western Anatolia - Akkaya, Gizem; Gürler, Orhan; Kahraman, Ayşegül; Yalcun, Sezai; Kaynak, Gokay (Springer Science and Business Media LLC, 2012)
Activity concentrations of gross-β, naturally occurring 226Ra, 232Th, 210Pb, 7Be and anthropogenic 137Cs in epiphytic lichens collected from Uludag Mountain are presented and discussed with the aim of evaluating potential usability of lichens as a biomonitor. The activity concentrations of gross-β, 137Cs, 40K, 226Ra, 232Th, 210Pb and 7Be in the lichen samples were found to be in the range of 177–707, 4.05–94.26, 86–211, below detection limit (BDL)—19.2, BDL—14.0, 229–872, and 72.1–220.7 Bq kg−1 in dry weight, respectively. 137Cs content in collected epiphytic lichens was in descending order: Parmelia sulcata > Lobaria pulmonaria > Pseudevernia furfuracea > Usnea filipendula. The best biomonitor for 137Cs among the lichen species used in this study was determined as Parmelia sulcata. Pearson’s correlation coefficient was calculated between 137Cs and 40K activity concentrations using a statistical package program (SPSS ver. 17.0) and a negative correlation value (R = −0,323, p = 0,222) was obtained. The highest 226Ra and 232Th activity concentrations were found in Bogazova Yaylasi which has a geological structure including granitic rocks. It was found that 137Cs and 7Be activity concentrations in species demonstrated an inverse behaviour. The effect of mean annual precipitation and temperature on 7Be activity concentration was determined using multi regression analysis. Also, correlations between the 137Cs and 7Be, and 40K and 7Be were investigated.